Tenofovir disoproxil fumarate co-administered with lopinavir/ritonavir is strongly associated with tubular damage and chronic kidney disease. Issue 7 (July 2018) - Mizushima, Daisuke; Nguyen, Dung Thi Hoai; Nguyen, Dung Thi; Matsumoto, Shoko; Tanuma, Junko; Gatanaga, Hiroyuki; Trung, Nguyen Vu; van Kinh, Nguyen; Oka, Shinichi
Abstract: Backgroud: With expanding antiretroviral therapy (ART) in a resource-limited setting, the use of second line ART with ritonavir boosted lopinavir (LPV/r) is increasing. However, little is known regarding the renal safety of tenofovir (TDF) co-administered with LPV/r. Methods: In total 1382 HIV-infected patients were enrolled and data were recorded twice (October 2014 and 2015) in Vietnam. Tubular dysfunction (TD) was defined as urinary beta 2 microglobulin (β2MG) > 1000 μg/L at both timepoints or increase in β2MG by > 2000 μg/L. Chronic kidney disease (CKD) was defined as creatinine clearance ≤60 ml/min or urinary protein/creatinine ratio ≥ 0.15 g/gCre at both timepoints. Results: The patients'mean weight and age were 55.9 kg and 38.4 years, respectively, and 41.5% were female. Additionally, 98.2% were on ART, 76.3% were on TDF (mean exposure duration was 35.4 months), and 22.4% had never TDF exposure. TD and CKD were diagnosed in 13% and 8.3% of all patients, respectively. In multivariate analyses, age (OR = 1.057; 95%CI, 1.034–1.081), being female (OR = 0.377; 95%CI, 0.221–0.645), HBsAg positive (OR = 1.812; 95%CI, 1.134–2.894), HCVAb positive (OR = 1.703; 95%CI, 1.100–2.635), TDF exposure (OR = 9.226; 95%CI, 2.847–29.901) and LPV/r exposure (OR = 5.548; 95%CI, 3.313–9.293) were significantly associated with TD. Moreover, age (OR = 1.093; 95%CI, 1.068–1.119), being female (OR = 0.510; 95%CI, 0.295–0.880), weight (OR = 0.909; 95%CI, 0.879–0.939), hypertension (OR = 3.027; 95%CI, 1.714–5.347), TDF exposure (OR = 1.963; 95%CI, 1.027–3.7 53) and LPV/r exposure (OR = 3.122; 95%CI, 1.710–5.699) were significantly associated with CKD. Conclusions: TDF and LPV/r exposure were strongly associated with TD and CKD, in addition to their known risks. Therefore, attention to renal safety for patients on second line ART is necessary.